Investment Decision Analysis Based on Stock Price Assessment with the Price Earning Ratio Approach on Consumer Goods Industry Sector Shares Listed on the Indonesia Stock Exchange - Gusvarizon, Muhammad; Ningsih, Putu Tirta Sari; Fanisa, Aldira (Universitas Mohammad Husni Thamrin, 2026)
This research is motivated by the large number of investors seeking to invest in stocks with optimal returns. Therefore, investors will conduct a stock assessment first. Investors can conduct stock research by analyzing the company's condition, both internally and externally. The stock analysis in this study focuses more on the company's internal assessment, often referred to as internal fundamental analysis. This also aligns with the research objectives of understanding the company's financial performance and the fairness of its stock. Determining the fairness of stock prices can be done through fundamental analysis using the Price Earning Ratio approach. The study selected samples from companies listed on the Indonesia Stock Exchange in the consumer goods industry sector from 2017 to 2019 using a purposive sampling method. From a population of 52 company stocks, six companies were sampled: PT. Indofood Sukses Makmur Tbk, PT. Indofood CBP Sukses Makmur Tbk, PT. Gudang Garam Tbk, PT. Handjaya Mandala Sampoerna Tbk, PT. Kalbe Farma Tbk, and PT. Tempo Scan Pacific Tbk. The company analysis used the Price Earning Ratio approach. The results of this study indicate that companies that are overvalued include PT. Indofood CBP Sukses Makmur Tbk and PT. Kalbe Farma Tbk, where the decisions that can be taken are to sell shares or hold shares if owned.